1977
DOI: 10.1530/acta.0.0850823
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO TEMPORAL cAMP AND CORTISOL RESPONSES TO ACTH BY THE NORMAL HUMAN ADRENAL GLAND

Abstract: The in vitro temporal cAMP and cortisol responses of normal human adrenocortical tissue to ACTH were evaluated. ACTH stimulated rapid increases in cAMP levels and cortisol output, however, significantly increased cAMP levels preceded steroid output only at the higher ACTH doses studied. Cortisol output plateaued with ACTH (10\p=n-\100 mIU/ml) while cAMP levels continued to increase. The findings indicate that the unitary role of cAMP as the second messenger of ACTH action in the human adrenal cannot be assumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…in the presence of external Ca2+(1.2mM) (Yanagibashi et al, 1978), this is identical to the data reported by other workers (Beall and Sayers, 1972;Mackie et al, 1972;Bowyer and Kitabchi, 1974;Honn and Chavin, 1977). It has been proposed that calcium may act at the sites before and beyond cyclic AMP formation as well as a direct effect of calcium on cyclic AMP formation (Bowyer and Kitabchi, 1974).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…in the presence of external Ca2+(1.2mM) (Yanagibashi et al, 1978), this is identical to the data reported by other workers (Beall and Sayers, 1972;Mackie et al, 1972;Bowyer and Kitabchi, 1974;Honn and Chavin, 1977). It has been proposed that calcium may act at the sites before and beyond cyclic AMP formation as well as a direct effect of calcium on cyclic AMP formation (Bowyer and Kitabchi, 1974).…”
Section: Resultssupporting
confidence: 87%
“…It is generally recognized by many workers that there is a definite dissociation between ACTH effects on corticoidogenesis and cyclic AMP formation in adrenal cortex (Beall and Sayers, 1972;Mackie et al, 1972;Bowyer and Kitabchi, 1974;Sharma et al, 1976;Honn and Chavin, 1977).…”
Section: Synopsismentioning
confidence: 99%
“…The concentrations of ACTH used and the steroid responses measured were similar to those previously observed in normal adrenal glands and in diced adrenal tissue from breast cancer patients. Honn and Chavin (17) found that a maximally stimulatory concentration of 3 nmol/L ACTH stimulated cortisol output to levels 4-5 times higher than control values. Most previous studies with human adrenal glands obtained from patients with Cushing's syndrome showed that (partial) autonomy of the adrenal gland in vivo is generally also reflected by the functions of cells or tissues incubated in vitro, in that they become less responsive to ACTH than normal tissue (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 93%